Injury Prevalence and Biomechanical Risk Patterns Kabaddi Players: A Positional Analysis - Sri Indah Ihsani; Made Bang Redy Utama; Saipulloh Ibrahim; Lita Mulia; Adi S; Muhammad Gilang Ramadhan; Ayu Purnama Wenly (Gladi : Jurnal Ilmu Keolahragaan, 2026)
Background: Kabaddi is a physically demanding contact sport that exposes youth athletes to high biomechanical stress, often resulting in injury. While positional roles in Kabaddi differ in movement patterns and physical demands, their association with injury prevalence among adolescent players remains underexplored. Objectives: This study aimed to investigate the prevalence and distribution of musculoskeletal injuries among youth Kabaddi players in Indonesia and to examine whether playing position, age, and experience contribute to injury risk. Methods: A cross-sectional survey was conducted involving 161 youth Kabaddi players aged 11–18 years across five regions. Injury data from the past 12 months and past 7 days were collected using a modified Oslo Sports Trauma Research Centre (OSTRC) questionnaire. Descriptive statistics and one-way ANOVA were performed to analyse differences in injury patterns based on player demographics and positions (All-rounder, Defender, Raider). Results: The most commonly injured regions were the shoulders, neck, and back, with no statistically significant differences in injury prevalence across playing positions (p > 0.05). However, older athletes (15–18 years) showed a significantly higher number of injuries compared to younger players (p < 0.05). Raiders reported the highest mean playing experience, while all-rounders were the oldest group. Despite biomechanical differences between roles, injury patterns appeared to be uniformly distributed. Conclusions: Injury prevalence among youth Kabaddi players is high and not confined to specific playing positions. This indicates that sport-wide preventive strategies, emphasizing core stability, neuromuscular control, and fatigue management, may be more effective than role-specific interventions. Findings reinforce the importance of biomechanical screening and integrated injury surveillance in youth Kabaddi development programs.